Field notes contributed by Joseph P. Schaufenbuel, winter 1981-1982 - Schaufenbuel, Joseph P.et al (1981)
Field notes were contributed by Joseph P. Schaufenbuel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1981-1982. Epson - sheet feed